Evaluation of water for an integrated water resources management in the Middle East: a social and territorial perspective - Minoia P. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
A fundamental step for protection and sustainable use of water resources is the consideration of their values either for sustaining human life and socio-economic functions, or for maintaining ecosystem health. The international debate is concentrated on two different approaches leading to a water sustainable management: the 'economic approach' introduced by the UN Dublin Conference (1992) and the 'humanitarian approach' stated by the UN Millennium Development Goals (2002). The two approaches have supported divergent views about the prioritisation of the water problems and the respective solutions, while they should instead be complementary for targeting different situations and sectors needs. Specific considerations will be presented on issues of relevance for the Mediterranean and the Middle East regions.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)